Femininities at work: How women support other women in the workplace - Carr, Melissa; Kelan, Elisabeth (British Academy of Management, 2016)
Recent research has highlighted the negative intra-gender relations that occur between women in organisations, focusing on aspects such as micro-violence, the queen bee syndrome, negative intra-gender relations, and competition and distance between women. Through a thematic analysis of interviews with 16 women, we draw on material where women were asked to consider their intra-gender relationships at work. We suggest that women are actively supporting each other and aligning themselves with each other; they are ‘mobilising femininities’ to help negotiate dominant hegemonic masculinity. However, the women also demonstrate contested femininities, creating distance from women who are not displaying an appropriate femininity. The article thereby examines the affiliated and contested femininities that women bring to bear in the workplace. It makes a contribution towards understanding mobilising femininities, the extent to which this is a conscious or liminal process for women and how, through mobilising femininities, gender as a social practice is demonstrated.